Low energy availability risk and in-season injuries among female adolescent athletes: A prospective cohort study over a school-season - Smulligan, K. L.; Brna, M. L.; Hogg-Cornejo, V.; Petersen, S.; Sweeney, E.; Meyers, R.; Howell, D. R.; Armento, A. M. (Physical Therapy in Sport, 2025)
Objective To prospectively examine the association between pre-season low energy availability (LEA) risk and injury rates among female adolescents during the subsequent athletic season.